Determinants of Birth Spacing Practice Among Parous Mothers - Isaac Harold; Joy Chinonyerem Amaechi; Pearl Chikasilamobu Ajie; Aniekan Isaac Harold (BioMed Target Journal)
Birth spacing is the interval between a live birth and a subsequent pregnancy, which is recommended to be at least two years. This study aimed to identify the determinants of birth spacing practices among parous mothers attending antenatal clinics in Port Harcourt, Nigeria. A cross-sectional study was conducted among 410 parous mothers aged 15–49 in Port Harcourt, Nigeria, from June to October 2024. A multistage sampling procedure was used to select the respondents, and data were collected using a semi-structured, interviewer-assisted questionnaire. Frequency tables were generated, and a binary logistic regression model was used to identify the determinants of birth spacing practices at a 5% significance level. The respondents’ mean age was 35.2 ± 3.9 years. The prevalence of birth spacing practice was 36.6%, with condoms (13.7%) being the most commonly used contraceptive method. Determinants such as attaining secondary education (OR = 1.9; 95% CI = 3.6–11.8; P = 0.00), tertiary education (OR = 1.5; 95% CI = 2.6–7.6; P = 0.00), employment status (OR = 2.4; 95% CI = 1.4–4.1 ; P = 0.00), knowledge of birth spacing (two-year interval (OR = 3.5; 95% CI = 1.6–7.4; P = 0.00), knowledge of the benefits of birth spacing (OR = 2.6; 95% CI = 3.7–46.4 P = 0.00), and spouse consent (OR = 3.8; 95% CI = 2.5–5.8; P = 0.00) significantly contributed to the practice of birth spacing among parous mothers.